Pertanggungjawaban Pidana Terhadap Pelaku Investasi Bodong (Kasus CV Raihan Jewellery) - Lisentia Putri; Hery Firmansyah (UNES Law Review, 2023)
Fraudulent investment is a form of crime where a certain amount of money is asked to invest in a product or business that does not ictually exist. Business in Indonesia is currently experiencing rapid development following the digital era, namely by utilizing technology to simplify the transaction process. The Indonesian financial services industry has utilized facilities called fintech. Companies and individuals also experience convenience in their business because they are assisted by fintech technology. However, in practice there are still many companies that use technology for illegal business, especially in the field of fraudulent investment with various kinds of schemes. The conditions for imposing criminal responsibility on perpetrators of online fraud are that all elements of the criminal act are fulfilled and the purpose of the act can be proven. This was done deliberately with awarenessm that the act would be condemned by law. To determine criminal responsibility for criminal acts of online buying and selling fraud, you must refer to specific laws, because to avoid misinterpretation if using conventional evidence and avoid the emergence of other interpretations, and there needs to be an understanding from law enforcers regarding the expansion of the evidence. In order to avoid misunderstandings, to have the same thoughts about the value of the evidentiary power of electronic evidence contained in the ITE Law.